Optimizing thermal diffusivity measurements for fluids with accessible 3D printing and Arduino-based temperature control - Miguel Ceja-Morales; Pedro E. García-González; Luis M. Montes-De-Oca; R.A. Medina-Esquivel; Miguel Zambrano-Arjona; Nikte M. Gomez-Ortiz; P. Martínez-Torres (HardwareX)
This study introduces an instrument to measure thermal diffusivity in fluids, called a Thermal Wave Resonator Cavity, constructed via additive manufacturing (3D printing) and significantly improved by integrating a temperature control system developed with an Arduino microcontroller. The device was assessed through measurement of the thermal diffusivity of distilled water both with and without temperature control. The results demonstrate that the temperature-controlled system yields significantly more reliable and reproducible thermal diffusivity measurements compared to the uncontrolled system. Furthermore, measurements of water’s thermal diffusivity at various temperatures corroborated values previously reported in the literature. This cost-effective and innovative solution leverages accessible technology to enhance the accuracy of thermal measurements, thereby democratizing access to traditionally expensive, high-quality scientific instruments. This approach has the potential to broaden research capabilities across various scientific disciplines by melding affordability with precision.